1996
DOI: 10.1016/s0005-2736(96)00172-1
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of cultured brain, adrenal, and aortic endothelial cell glucose transport

Abstract: Studies of glucose transporter activity and anti-glucose transporter (GLUT1) immunoblots were performed on different endothelial cell primary cultures (brain capillary, adrenal capillary and aortic) to determine their response to glucose deprivation. Cell cultures were exposed to glucose deprivation (0.5 mM) for 48 h periods and refed (11.0 mM) for 36 additional hours. Control cultures were kept in 11.0 mM glucose for the duration of these studies. Measurements of 2-[3H]deoxy-D-glucose uptake and membrane frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Glucose oxidase (GOX) does not only consume oxygen but also leads to depletion of glucose in the incubation medium. Previous studies investigating in vitro FDG uptake in various cell lines have revealed that hypoglycemic conditions lead to an increased FDG uptake [31,32]. Furthermore, it has been shown that the enhanced transport activity caused by hypoglycemia is attributed to an increased expression of GLUT1 in the cell membrane [33].…”
Section: Discussionmentioning
confidence: 99%
“…Glucose oxidase (GOX) does not only consume oxygen but also leads to depletion of glucose in the incubation medium. Previous studies investigating in vitro FDG uptake in various cell lines have revealed that hypoglycemic conditions lead to an increased FDG uptake [31,32]. Furthermore, it has been shown that the enhanced transport activity caused by hypoglycemia is attributed to an increased expression of GLUT1 in the cell membrane [33].…”
Section: Discussionmentioning
confidence: 99%
“…Erythrocytes and endothelial cells, however, transport glucose some 50- to 500-fold more rapidly than they utilize sugar (203, 284). In spite of this, red cells respond to ATP depletion with 4- to 10-fold increased glucose uptake (153), endothelial cells respond to acute hypoglycemia with increased V max for net sugar uptake (142) and respond to chronic hypoglycemia or hypoxia with increased GLUT1 expression (194, 373, 396) resulting in enhanced (1.5 to 2-fold) glucose uptake (558). Why regulate transporter activity or content in cells where glucose supply exceeds demand?…”
Section: Transport Regulationmentioning
confidence: 99%
“…, 2016 ). GLUT1 is also abundantly expressed in endothelial cells of brain, aorta, and adrenal microvessels ( Gaposchkin and Garcia-Diaz, 1996 ). The use of radioactive and fluorescent glucose derivatives of glucose allowed us to identify uptake via these transporters as well as a dynamic uptake via endocytosis.…”
Section: Discussionmentioning
confidence: 99%